A facile preparation method for new two-component supramolecular hydrogels and their performances in adsorption, catalysis, and stimuli-response. Issue 39 (22nd July 2019) - Zhu, Junlin; Wang, Ran; Geng, Rui; Zhang, Xuan; Wang, Fan; Jiao, Tifeng; Yang, Jingyue; Bai, Zhenhua; Peng, Qiuming
Abstract : New two-component supramolecular hydrogels were prepared via a self-assembly process, demonstrating potential applications in adsorption and catalysis as well as sensor materials. Abstract : In this study, we prepared a novel multifunctional two-component supramolecular hydrogel (T-G hydrogel) via two organic molecules in ethanol/water mixed solvents. In addition, we prepared gold nanoparticle/T-G (AuNPs/T-G) composite hydrogels using T-G hydrogel as a template for stabilizing AuNPs by adding HAuCl4 and NaBH4 during the heating and cooling process of T-G hydrogels. The morphology and microstructure of the as-prepared hydrogels were characterized using SEM, TEM, XRD, and FT-IR. The hydrogels prepared by solutions that contained different ethanol/water volume ratios exhibited different microstructures, such as sheets, strips, and rods. The obtained T-G hydrogels exhibited a sensitive response to pH changes in the process of sol–gel transformation and showed good adsorption properties for model organic dyes. In the presence of NaBH4, the obtained AuNP/T-G composite hydrogels exhibited the excellent catalytic performance for 4-nitrophenol (4-NP) degradation. Thus, the current research provides new clues in developing new multifunctional two-component supramolecular gel materials and exhibits potential applications for wastewater treatment.